THE MODERN AREA OF DISTRIBUTION AND LIFE FORMS OF RUSSIAN OLIVE (ELAEAGNUS ORIENTALIS L.), AND THE ORIGIN OF ITS CULTIVATED FORMS - Kh. K. Hajdarov (Труды по прикладной ботанике, генетике и селекции)
The article considers modern species of the genus Elaeagnus L. and life forms of E. orientalis L. in Uzbekistan. There are two types of sympodial (acrosympodial and mesosympodial) growth. Additionally, the origin of the cultivated forms of Russian olive in Central Asia is discussed.